Organization Justice and Job Satisfaction Among Teachers of Self-Financing Arts And Science Colleges In Thrissur District, Kerala. (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Correlation Among Organisational Justice And Work Performance Is Explored In This Proposed Study. Organizational Justice Is Historically Assessed By Three Components. In This Paper, The Model Of Corporate Fairness Has Been Enlarged And The Components Of Spatial And Temporal Fairness Are Studied And Evaluated. The Implication Of Organisational Justice On Work Satisfaction Has Been Measured In Five Components. The Researcher Has Used Structured Questionnaire To Collect Data From 268 Samples Of Self-Financing Arts And Science Colleges In Thrissur District. Proportionate Stratified Random Sampling Method Has Been Adopted. In Order To Ensure Validity, The Investigator Incorporated Descriptive And Inferential Statistics. Teachers’ Expectations Have Been Used To Determine Whether Or Not Justice Prevails In The Institution And Whether This Fairness Influences Their Level Of Job Satisfaction. The Discoveries Have Established A Great Connection Between Work Satisfaction And Organisational Fairness.